A Novel Method Enables General Pathologists to Create Web Dynamic Forms for Synoptic Tumor Reporting. - Zhenhong Qu; Keran Zhao; Guo Jin, Jason; Qu, Elaine; Zongshan Lai (Archives of Pathology & Laboratory Medicine, 2021)
* Context.--Tumor reporting constitutes a significant daily task of pathologists. An efficient tumor-reporting methodology is thus vitally important. The Web dynamic form (WbDF) method offers a multitude of advantages over the prevailing transcription-mediated reporting method based on static-text checklists. However, its adaptation has been severely hampered for 2 decades by its costly needs to maintain a complex back-end system and to change the system for frequent updates of reporting content. Objective.--To overcome these 2 obstacles with a serverless Web platform that enables users to create, customize, use, and download WbDFs as synoptic templates for structured tumor reporting. Design.--Deploy ReactJS as a Web platform. Create form components in JavaScript Object Notation files. Use JavaScript Object Notation files to make WbDFs on the Web platform. Use the WbDFs to generate final pathology reports. Results.--Ordinary users (pathologists) can create/customize reporting templates as WbDFs on the Web platform. The WbDF can be used to make a pathology report and stored/shared like ordinary document files. There is no back-end system to change, nor a requirement for computer programming skills. Conclusions.--This strategy eliminates the need for a complex back-end system and the associated cost when updating tumor-reporting standards, making it possible to adopt the WbDF method without the technological drawbacks associated with content updates. It also opens a new field of how the tumor-reporting system should be organized, updated, and implemented.